Konflik, etnisitas dan integrasi nasional - Suharno Suharno (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
This paper lift up some important issues linked to conflict, ethnicity, and national integration on our world today. Main focus is why conjlict based on ethnic and ethnic identity raised on our world today. The center of criticism will be explored in this paper. Beside, this paper also gives some important notion to maintain nationality owned by the ethnic group, especially Indonesia in multiethnic condition which has a big risk and potential of being crashed by ethnic conflict and disintegration.